2006
DOI: 10.1200/jco.2006.05.8768
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Repair Gene Polymorphisms Predict Favorable Clinical Outcome Among Patients With Advanced Squamous Cell Carcinoma of the Head and Neck Treated With Cisplatin-Based Induction Chemotherapy

Abstract: Using a multivariate model, the presence of polymorphic variants in DNA-repair genes are powerful prognosis factors and response to cisplatin predictors among SCCHN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 35 publications
11
111
3
3
Order By: Relevance
“…Melanoma patients with the wild-type genotype treated with cisplatin, however, had shorter survival rates and worse response [45]. Additionally, it has been shown that increased variant alleles in ERCC2 and XRCC1 confer a worse survival for non-small cell lung cancer patients treated with platinum drugs [8], whereas an increasing number of variant alleles in squamous head and neck cancer treated with cisplatin had increased survival rates [22]. Even though there are a few identified genetic predictors of platinum-based treatment outcome in DNA repair genes, there is a paucity of data on genetic variants important in platinum-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma patients with the wild-type genotype treated with cisplatin, however, had shorter survival rates and worse response [45]. Additionally, it has been shown that increased variant alleles in ERCC2 and XRCC1 confer a worse survival for non-small cell lung cancer patients treated with platinum drugs [8], whereas an increasing number of variant alleles in squamous head and neck cancer treated with cisplatin had increased survival rates [22]. Even though there are a few identified genetic predictors of platinum-based treatment outcome in DNA repair genes, there is a paucity of data on genetic variants important in platinum-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate gene approaches have been implemented to identify the basis of response or toxicity to cisplatin, which have included the use of tumor cell types and model systems [18][19][20]. Variants in candidate genes such as glutathione S-transferases, ERCC1, ERCC2, and XRCC1 have been shown to alter response to cisplatin [21,22]. Candidate gene studies with these variant alleles, however, have also lead to inconsistent results [21].…”
Section: Introductionmentioning
confidence: 99%
“…All these SNPs have been related to platinum and radiotherapy response and/or risk of cancer in other type of tumors. [9][10][11][12]24,30,31 Genotypes were determined by TaqMan SNP Genotyping Assays (Applied Biosystems, Foster City, CA, USA) for all SNPs, except rs1800975 (or which the KASPar SNP genotyping system was used (KBioscience, Hoddesdon, UK). Allelic discrimination was carried out using the ABI PRISM 7900 Sequence Detection System (Applied Biosystems).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Alterations in NER genes expression 8 as well as the presence of single nucleotide polymorphisms (SNPs) 9 are correlated with cisplatin resistance. SNPs in the ERCC1 and ERCC2 10 genes have been found to be associated with platinum response in different clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of NER capacity has been demonstrated in testicular cancer (10), where it may have important implications for susceptibility to cisplatinum-based chemotherapy (11). NER gene polymorphisms have been associated with response to cis-platinum in head and neck (12), lung (13), and breast cancer (14). Constitutively low NER levels have been reported in the peripheral blood lymphocytes (PBLs) of patients with breast cancer (15,16) and their relatives (17).…”
mentioning
confidence: 99%